Revision Surgery Occurs Frequently After Percutaneous Fixation of Stable Femoral Neck Fractures in Elderly Patients - Kain, Michael S. (Clin Orthop Relat Res, 2014)
BACKGROUND: Femoral neck fractures are a major public health problem. Multiple-screw fixation is the most commonly used surgical technique for the treatment of stable femoral neck fractures. QUESTIONS/PURPOSES: We determined (1) the proportion of hips that had conversion surgery to THA, and (2) the proportion of hips that underwent repeat fracture surgery after percutaneous screw fixation of stable (Garden Stages I and II) femoral neck fractures in patients older than 65 years and the causes of these reoperations. METHODS: We performed a retrospective study of all patients older than 65 years with stable femoral neck fractures secondary to low-energy trauma treated surgically at our institution between 2005 and 2008. We identified 121 fractures in 120 patients older than 65 years as stable (Garden Stage I or II); all were treated with percutaneous, cannulated screw fixation in an inverted triangle without performing a capsulotomy or aspiration of the fracture hematoma at the time of surgery. The average age of the patients at the time of fracture was 80 years (range, 65–100 years). Radiographs, operative reports, and medical records were reviewed. Fracture union, nonunion, osteonecrosis, intraarticular hardware, loss of fixation, and conversion to arthroplasty were noted. Followup averaged 11 months (range, 0–5 years) because all patients were included, including those who died. The mortality rate was 40% for all patients at the time of review. RESULTS: Twelve patients (10%) underwent conversion surgery to THA at a mean of 9 months after the index fracture repair (range, 2–24 months); the indications for conversion to THA included osteonecrosis, nonunion, and loss of fixation. Two others had periimplant subtrochanteric femur fractures treated by surgical repair with cephalomedullary nails and two patients had removal of hardware. CONCLUSIONS: Revision surgery after osteosynthesis for stable femoral neck fractures was more frequent in this series than previously has been reported. The reasons for this higher frequency of reoperation may be related to poor bone quality, patient age, and some technical factors, which leads us to believe other treatment options such as nonoperative management or hemiarthroplasty may be viable options for some of these patients. LEVEL OF EVIDENCE: Level IV, therapeutic study.